The HydroGeo Software Package and Its Usage; E3S Web of Conferences; Vol. 98 : 16th International Symposium on Water-Rock Interaction (WRI-16) and 13th International Symposium on Applied Isotope Geochemistry (1st IAGC International Conference) - Dutova E. M. Ekaterina Matveevna (2019, 2019)
Title screen